2012
DOI: 10.1039/c2cp40501f
|View full text |Cite
|
Sign up to set email alerts
|

Are lithium and sodium salts of N-(2-hydroxyphenyl)-salicylaldimine aromatic metalla-hetero[10]annulenes? An answer given by spatial magnetic properties (through space NMR shieldings—TSNMRS)

Abstract: The spatial magnetic properties (through space NMR shieldings-TSNMRS) of the enol tautomer of N-(2-hydroxyphenyl)-salicylaldimine, the lithium and sodium salts in comparison with cyclodecapentaene and pyrano[2,3-b]pyrrole were studied to answer this question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Specifications normally employed from magnetic point of view to quantify, e. g ., (anti)aromaticity, are theoretical non‐measurable items: single NICS values or components of the latter, or traces of NICS or components of the latter starting from the centre of the (anti)aromatic compound up to 10 Å outwards. Experimental Δδ/ppm in proton NMR spectra, in turn, are the molecular response property of our TS NMRS values . For this latter reason, the spatial magnetic properties (TS NMRS values) of 12 H ‐benzo[ a ]xanthen‐12‐one 11 (and, vide infra , of the preferred conformers/diastereomers of the new O , N ‐ and N , N ‐heterocycles) have been calculated and examined with respect to (i) the combined ring current effect of the C‐7a to 11a phenyl residues and the anisotropy effect of the carbonyl moiety on the chemical shift of H‐1 in 11 ( cf .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifications normally employed from magnetic point of view to quantify, e. g ., (anti)aromaticity, are theoretical non‐measurable items: single NICS values or components of the latter, or traces of NICS or components of the latter starting from the centre of the (anti)aromatic compound up to 10 Å outwards. Experimental Δδ/ppm in proton NMR spectra, in turn, are the molecular response property of our TS NMRS values . For this latter reason, the spatial magnetic properties (TS NMRS values) of 12 H ‐benzo[ a ]xanthen‐12‐one 11 (and, vide infra , of the preferred conformers/diastereomers of the new O , N ‐ and N , N ‐heterocycles) have been calculated and examined with respect to (i) the combined ring current effect of the C‐7a to 11a phenyl residues and the anisotropy effect of the carbonyl moiety on the chemical shift of H‐1 in 11 ( cf .…”
Section: Resultsmentioning
confidence: 99%
“…This is in no case remarkable. The experimental proton chemical shift δ( 1 H)/ppm is the molecular response property of the spatial magnetic properties TS NMRS ( e. g ., the anisotropy/ring current effect) . Both the chemical shift difference between the phenyl protons in the cis ( 17 a ) and the trans diastereomer ( 32 b ) [Δδ(H‐5′‐H‐4)=0.07 ppm, Δδ(H‐4′‐H‐3=−0.07 ppm] and the calculated ring current effects [Δδ(H‐5′‐H‐4)=‐0.34 ppm, Δδ(H‐4′‐H‐3=+0.02 ppm] are comparable.…”
Section: Resultsmentioning
confidence: 99%
“…In other complexes studied and where chelatoaromaticity was assumed (acetylacetonato chelato complexes, metallobenzenes complexes, orthohydroxy-para-pyrone chelato complexes and the molybdenum dithiolene complex 20a) [77] as well as in the corresponding free ligands chelatoaromaticity could not be identified [77]. Herefrom can be concluded that approving the lithium and sodium salts of N-(2-hydroxyphenyl)salicylaldimine as the first example of metalla-hetero [10]annulene goes too far [78] and when evaluating aromaticity [80,81], which is a multidimensional characteristic [81] dependent on energetic, geometric and magnetic criteria [82,83], that all items must be considered. Scheme 3.11), the magnetic criteria (spatial magnetic properties-TSNMRS) were studied in order to compare with previous results (cf.…”
Section: Chelatoaromaticity and Miscellaneous Aromaticitymentioning
confidence: 97%
“…36 Visualization of the magnetic properties (TSNMRS) of N-(2-hydroxyphenyl) salicylaldimine 21 (left) and 1,3-dihydroxy-naphthyl-2-aldehyde 24 as ICSS of different direction and size. Reproduced by permission of the PCCP Owner Societies[78].…”
mentioning
confidence: 99%
“…Employing the same methodology [38,39], the preferred quinoid type structure of a bridged bisphenazine type molecule 19 could be assigned [43] (Scheme 5.13). On the other hand, employing the same methodology again [38,39], the enol form and the lithium and sodium salts of N(-2-hydroxyphenyl)-salicylaldimine could be readily identified to be not the first example of metalla-hetero[10]annulenes [44].…”
Section: Scheme 511mentioning
confidence: 97%